Optimizing the spectro-temporal properties of photon pairs from Bragg-reflection waveguides. (2nd April 2019) - Chen, H; Laiho, K; Pressl, B; Schlager, A; Suchomel, H; Kamp, M; Höfling, S; Schneider, C; Weihs, G
Abstract: Bragg-reflection waveguides (BRWs) fabricated from AlGaAs provide an interesting nonlinear optical platform for photon-pair generation via parametric down-conversion (PDC). In contrast to many conventional PDC sources, BRWs are made of high refractive index materials and their characteristics are very sensitive to the underlying layer structure. First, we show that the design parameters like the phase matching wavelength and the group refractive indices of the interacting modes can be reliably controlled even in the presence of fabrication tolerances. We then investigate how these characteristics can be taken advantage of when designing quantum photonic applications with BRWs. We especially concentrate on achieving a small differential group delay between the generated photons of a pair and then explore the performance of our design when realizing a Hong–Ou–Mandel interference experiment or generating spectrally multi-band polarization entangled states. Our results show that the versatility provided by engineering the dispersion in BRWs is important for employing them in different quantum optics tasks.